The educational impact of implementation the education through adventure discipline in physical education and sports academic curriculum - D. Badau (Physical Education of Students)
Introduction: The inclusion in the curriculum for students of physical education specialization in Romania of a new discipline- Education through adventure (EA) falls within the current trends of practicing physical activities and modernization of the European curriculum. Purpose: The purpose of the study aims at assessing the educational level of implementation of EA discipline within the academic curriculum of physical education and sport specialization. Material and Methods: Study through the survey method based on a questionnaire concerning the assessment of the educational impact of implementing the EA disciplines. Participants: 72 students from physical education, University of Medicine and Pharmacy Targu Mures. The questionnaire on the assessment of the educational impact of implementing the EA discipline included 15 items with Linckert responses. Statistically processed with SPPS 20: Cronbach's alpha, effect size, the percentage of individual qualifications, the arithmetic mean, the standard deviation, t-test. Results: The 15-item questionnaire had a Cronbach reliability scores .792. We identified five patterns that emerged explaining more than 60.2% of the variance. 54.82% consider relevant the educational discipline with maximum response, effect size of each ≥.683 items, the results are statistically significant for all items, p <0.05. The study results reveal the major educational impact of EA discipline content, being considered by students as it follows: attractive, useful, effective with innovative relevance in the professional training. Conclusions: We recommend the conduct of future studies of impact assessment of EA specific activities on students’ motor abilities.